Beyond Messiaen's birds: the post-verbal world of dementia. Issue 1 (29th May 2019) - Wood, Stuart
Abstract : This paper investigates the use of verbatim musical transcription as a research method in dementia care. It reports on an art-based ethnographic study (Aesthetic Research in Everyday Life (Aeriel)) in which verbatim transcription was applied to everyday interactions in dementia care, making use of musical—instead of verbal—notation. Starting from the notion that medical and healthcare settings can be sites of 'found performance', the paper reviews literature relating to artistic methodologies within medical humanities, music, ethnography and dementia care. From this review, it proposes a research design and method of verbatim musical transcription as a potential avenue of investigating communication between carer and cared for in dementia care. The paper offers an illustrative example from Aeriel and draws conclusions from the synthesis of verbal and musical data analysis. Findings indicate an important advance in studies of dementia care communication towards a concept of the 'post-verbal' enabled by a musical research method and the clinical applications that it offers.